Pelatihan Pemanfaatan Limbah Tongkol Jagung Untuk Pembudidayaan Jamur Kuping Bagi Kelompok Ibu Rumah Tangga Di Perkotaan: id - Andi Muhammad Taufik Ali; Paloboran, Marthen; Muflihat, Syakia (Program Studi Sarjana Terapan PTM FT UNM, 2025)
The increasing consumption of corn in Makassar City generates abundant corn cob waste from households and SMEs (UMKM), which potentially pollutes the environment. This community service program aims to address the waste problem while simultaneously creating a sustainable new business opportunity for housewives. The method employed was training and practical demonstration of black ear mushroom cultivation using corn cobs as the growing medium for the BKMT Annisa Hidayah Women's Group in Mannuruki Village, Makassar, on August 23, 2025. The training covered waste potential counseling, growing media formulation, cultivation management, and harvesting methods. The activity was successfully implemented with high enthusiasm. Practical results show that the women were able to yield an initial harvest of 5–6 Kg per batch, which was successfully marketed at prices ranging from Rp35,000–Rp40,000 per Kg through social media. In conclusion, this program is effective in improving skills, creating profitable home-based business opportunities, and providing a positive impact on environmental sustainability by converting waste into a product of economic value.